A novel approach to investigate the pore network and clogging of pervious concrete - Xiang Zhang; Longhui Dong; Wenjie Yu; Enzhong Ren; Runzhu Shi (Case Studies in Construction Materials)
The long-term service of pervious concrete may result in the internal pore network becoming clogged by particles, which could lead to a reduction in infiltration rate and service life. It is therefore essential to consider the pore structure of pervious concrete and to investigate the fluid migration. In the present study, pervious concrete specimens with porosities of 15 % (G1), 20 % (G2), and 25 % (G3) were prepared. Experimental results show that the clogging rates of G1 are 78.77 % and 80.59 % with sand particles of 0.15–0.3 mm and 0.3–0.6 mm, respectively. For G2, the clogging rates with particles of 0.3–0.6 mm and 0.6–1.18 mm are respectively 89.86 % and 89.72 %. Similar to G2, particles of 0.3–1.18 mm dominate the fluid migration in G3. Based on the NMR test, the pore space models were generated through the biphasic change on Gaussian random field. Numerical calculation scenarios comprising image analysis operations of mathematical morphology were proposed to validate the models and to study the issue of clogging, and the related parameters, including path length, tortuosity, pore throat size and interconnected porosity, were obtained. The results indicate that for G1, G2 and G3, the particle size ranges causing clogging fall respectively between 0.45 and 0.75 mm, 0.6–1.0 mm, and 1.125–1.575 mm. Different from previous studies, pore space models were constructed without initial pore shape setting, and the clogging particle size ranges were numerically obtained using mathematical morphology methods in this work. The obtained results are beneficial for a more comprehensive understanding of the internal structure and infiltration characteristics of pervious concrete.